An Extended Car-Following Model considering the Driver's Desire for Smooth Driving and Self-Stabilizing Control with Velocity Uncertainty. (29th August 2020) - Li, Shihao; Wang, Ting; Cheng, Rongjun; Ge, Hongxia
Abstract : In this paper, an extended car-following model with consideration of the driver's desire for smooth driving and the self-stabilizing control in historical velocity data is constructed. Moreover, for better reflecting the reality, we also integrate the velocity uncertainty into the new model to analyze the internal characteristics of traffic flow in situation where the historical velocity data are uncertain. Then, the model's linear stability condition is inferred by utilizing linear stability analysis, and the modified Korteweg-de Vries (mKdV) equation is also obtained to depict the evolution properties of traffic congestion. According to the theoretical analysis, we observe that the degree of traffic congestion is alleviated when the control signal is considered, and the historical time gap and the velocity uncertainty also play a role in affecting the stability of traffic flow. Finally, some numerical simulation experiments are implemented and the experiments' results demonstrate that the control signals including the self-stabilizing control, the driver's desire for smooth driving, the historical time gap, and the velocity uncertainty are of avail to improve the traffic jam, which are consistent with the theoretical analytical results.